Kinetics and mechanism of aquation of bromopentammine cobalt(III) cation assisted by ion-pairing succinate anion in ethane-2-diol-water mixtures - Ismail, Amel Moustafa; Seleim, Seleim Mohamed; Zaghloul, Amal Abd-El-Hamid; Amira, Mohamed Fawzy (European Journal of Chemistry, 2012)
The aquation kinetics of bromopentammine cobalt(III) ion has been investigated in the presence of different concentrations of succinate ion in aqueous medium and that mixed with ethane-1,2-diol (up to 50%, w/w) within the temperature range (35-65 oC). The ion-pairing succinate ion concentration (L) and the observed rate constant have been determined at different experimental conditions. The thermodynamic parameters of activation have been calculated and discussed in terms of solvent effects. Also the extrathermodynamic analyses of the obtained results have been discussed on the basis of solute-solvent and solvent-solvent interactions. An empirical correlation between the rate coefficient and the concentration of the ion-pairing succinate ligand (L) has been established and a suggested reaction mechanism is proposed.